Case Report: Pengaruh Stimulasi Taktil-Kinestetik dan murotal Al Quran terhadap Respirasi, Saturasi Oksigen dan Heart Rate pada Neonatal Respiratory Distress di Ruang PICU/NICU RSUD TJITROWARDOJO - Fenna Ayuningtyas; Falasifah Ani Yuniarti; Rina Prawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Increased oxygen reliance within the first 24 hours, no illness symptoms, typical radiological findings with lower air content, pulmonary reticulogranular pattern, and air bronchogram are all associated with respiratory distress syndrome, or RDS. Body weight and gestational age have an inverse relationship with the occurrence of RDS. RDS affects 15–30% of newborns born between 32 and 36 weeks and 60–80% of babies born less than 28 weeks. Although it is uncommon, RDS can develop after 36 weeks or term; alternative diagnosis should be explored. Objective: To determine the effectiveness of kinesthetic tactile stimulation therapy and murrotalAl Quran therapy in babies diagnosed with respiratory distress syndrome. Method: This type of research is descriptive research using a case study method approach. Results: The results of the nursing intervention that was carried out in the form of giving kinesthetic tactile stimulation therapy to babies for 5 consecutive days which were carried out for 20 minutes showed that there were changes in oxygen saturation, pulse and breathing became more stable than before the intervention was given.